Validation of FUNMOVES: A reliable tool for assessing motor skills in Spanish schoolchildren - Pablo Lizoain; Diana Rodriguez Romero; Celeste Reyes-Vivanco; Nick Preston; Lucy H. Eddy; Liam J. B. Hill; Sara Magallón; Martín Martínez (PLoS ONE, 2025)
Background Developmental Coordination Disorder (DCD) affects around 5% of the global population, but difficulties in accessing specialist diagnoses lead to underdiagnosis. In Spain, there are no school-based screening protocols for motor coordination difficulties with published evidence of reliability and validity, and specialist assessment is only available through overburdened healthcare services. Despite its prevalence, DCD often goes undetected due to limited access to assessments and the lack of easy-to-use tools in educational settings. FUNMOVES was developed to assess fundamental motor skills (FMS) and has shown promising signs of validity and reliability in the UK. It allows entire classes to be screened during a single Physical Education (PE) session, helping identify children with motor difficulties. Aim To adapt FUNMOVES to the Spanish school context and evaluate its psychometric properties and diagnostic accuracy when used by PE teachers. Methods FUNMOVES was translated and culturally adapted for Spain. Structural validity was assessed using Rasch analysis with data from 243 children. Convergent validity was evaluated in a subsample of 50 children by comparing FUNMOVES with the MABC-2, the gold-standard motor assessment. Results Rasch analysis confirmed the unidimensionality and local independence of the Spanish FUNMOVES, with good model fit. Some item thresholds were initially disordered but were corrected through rescoring. Using the MABC-2 10 th percentile in total score as the criterion for motor impairment, FUNMOVES showed moderate accuracy (AUC = 0.78), with 80% sensitivity and 68% specificity at the 17 th percentile cut-off. It also showed a high negative predictive value (0.89). Broadening the diagnostic criteria did not significantly improve accuracy. Implications The Spanish FUNMOVES shows initial structural and convergent validity for school-based FMS screening. Its simplicity, low cost, and scalability support early detection and intervention. The tool is freely available and can be implemented using existing school resources in one PE session, potentially accelerating the diagnostic process.